Neurofeedback and brain-computer interface: development and evaluation of a game designed to help in the detection of ADHD (Research, Society and Development, 2022)
Neuropsychological assessment uses interviews, observations, and the application of tests to assist in the investigation and diagnosis process. Some technologies have emerged to assist neuropsychological assessment and therapy, such as neurofeedback. We describe the construction process of a neurofeedback game with a Brain-Computer Interface wireless aimed at helping the detection of ADHD (Attention Deficit Hyperactivity Disorder). Two children, one with and one without the disorder, tested the tool. Regarding usability, the experiments showed that both five-year-old participants could fully use the game, performing all the tasks contained in it. The EEG wave behaviors obtained by the solution for the child who had the disorder were like those of ADHD patients found in other studies. In particular, the data generated showed alpha-type activities more frequently in children with ADHD.